ADHESIONS OF THE LABIA MINORA IN YOUNG GIRLS: WHAT A PEDIATRIC GYNECOLOGIST SHOULD DO - Z. K. Batyrova; E. V. Uvarova; L. S. Namazova-Baranova; N. H. Latypova; A. E. Donnikov ("Paediatrician" Publishers LLC, 2012)
Adhesion of the labia minora is one of the most complicated diseases in girls at the age beginning with infancy. The occurrence of this condition in population is 0,6-3% of girls. It mainly can be found at the age of from 3 months to 6 years, the age from 12 to 23 months is the peak of disease prevalence. The relapse rate varies from 14 to 39%. During last decade the prevalence of disease has been reported to rise significantly. However there is lack of uniform guidelines of children with this condition management both in Russia and abroad. In this article the problem of management of infant girls with adhesions of the labia minora is highlighted, the advantages and disadvantages of various treatment options are discussed.